(untitled) (Baghdad Science Journal, 2025)
In this work, a series of new maleimides linked to substituted benzothiazole moiety were synthesized. Synthesis of these new cyclic imides were performed via three steps, the first one involved preparation of a series of 2-aminobenzothiazole substituted with different substituents via reaction of different primary aromatic amines with ammonium thiocyanate and bromine in glacial acetic acid. The prepared 2- amino benzothiozoles were introduced in the second step in reaction with maleic anhydride producing a series of N-(substituted benzothiazole-2-yl) maleamic acids.The resulted maleamic acids were dehydrated in the third step via treatment with acetic anhydride and anhydrous sodium acetate to afford a series of the desirable N-(substituted benzothiazole -2-yl) maleimides.The synthesized maleimides were screened for thier antibacterial activity against two types of bacteria including (staphylococcus aureus) Gram positive and (Klebsiella pneumoniae) Gram negative bacteria respectively.Antifungal activity of the prepared imides also were tested against (Candida albicans) fungi.The new compounds were found to exhibit good antibacterial and antifungal activities.